Crustal deformation of Eastern Indonesia regions derived from 2010-2018 GNSS Data. Issue 1 (October 2021) - Rahmadani, Suchi; Meilano, Irwan; Sarsito, Dina A.; Susilo,
Abstract: Eastern Indonesia lies in a complex tectonic region due to the interaction of four major tectonic plates: the Australian Plate, Pacific Plate, Philippine Sea Plate, and Sunda Block. Therefore, this region hosted some destructive seismic activities as well as tectonic deformation, such as the Mw 7.5 Palu Earthquake, the sequences of the 2018 Lombok Earthquake, and the Mw 6.5 Ambon Earthquake in 2019. Our work proposes a recent study on crustal deformation in Eastern Indonesia inferred from Global Positioning System (GPS) velocity field. We used GPS data from the observations of 49 permanent and 61 campaign stations from 2010 to 2018. Here, our velocity field result represents long-term tectonic deformation regions in Eastern Indonesia continuously, from Bali in the west to Papua in the east, demonstrated both in the ITRF 2008 and the Sunda reference frames. The spatial pattern of velocity field map collected from this research will give an initial insight into the present-day tectonic condition in Eastern Indonesia and then can be used to improve our ability to assess this area's earthquake potential.